Estimation of Wire Closeness of Power Station Switch-Gear in terms of Allowable Impulse of Electrodynamic Forces - I. I. Sergey; E. G. Ponomarenko; Wail Mahmood Sammour (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper contains description of the method how to estimate switch-gear wife closeness. This method is based on the usage of electrodynamic force impulse. An approximate formula is deduced for determination of allowable value in respect of phase closeness of electrodynamic force impulse. The paper has made it possible to obtain an additional condition for estimation of non-allowable phase closeness of flexible buses in terms of design and allowable values of electrodynamic force impulse. Certainty of calculations has been estimated with the help of BUSEF computer program.